The formation of Tutelary Counselors in three municipalities in the metropolitan region of São Paulo (Research, Society and Development, 2021)
In order to understand how the people who work at Conselho Tutelar (Guardianship Council) are instructed and the work dynamics in behalf of the rights of children and adolescents, from the perspective of the guardianship counselors, this descriptive, interpretive, qualitative study was carried out, which was based on the methodological postulates of Oral History. Fifteen counselors of the metropolitan region of the city of São Paulo were surveyed. Individual semi-structured interviews were conducted between 2018 and 2019, in the Guardianship Council own space. The data were analyzed by content analysis. Two categories emerged from the study of the interviews: 1) Training and qualification of the counselors to work in the Guardianship Council; 2) Work dynamics. The importance of the Guardianship Council and its attributions in society became evident from the results of this study, contributing to guarantee the rights of children and adolescents. Nevertheless, there is still little knowledge, preparation and training of counselors to perform their duties, which has consequences for the performance of their role and for the well-being of children and adolescents who need help. Adolescent Health